Synthesis and antimicrobial activity of some new 1,2-bis-[1,3-thiazolidin-3-yl]ethane derivatives - Dawood, Kamal Mohamed; Abu-Deif, Hussein Khalaf-Allah (European Journal of Chemistry, 2013)
1,2-Bis-(2-(phenylimino)-4-oxo-1,3-thiazolidin-3-yl)ethane (4) was synthesized and its reaction with various aldehydes afforded the novel 5-arylidene derivatives 5a-e and 7. Reaction of compound 4 with phenyl isothiocyanate in the presence of potassium hydroxide, followed by addition of two equivalents of α-halo ketones furnished the corresponding 1,2-bis-[5-(thiazolidin-2-ylidene)thiazolidin-3-yl]ethane derivatives 10, 14a-c, and 17a,b. The structures of the newly synthesized compounds were established by elemental and spectral analyses. Compounds 5a-e, 7, 10, 14a-c and 17a were screened for their antimicrobial activity against eight microorganisms. All compounds showed high antibacterial and antifungal activities against all the test microorganisms except E. coli and C. albicans. The MIC of the active compounds was also evaluated, where; compounds 10 and 17a were more potent active (minimum inhibitory concentration 0.49 and 0.98 μg/mL, respectively) against S. racemosum than Amphotericin B (MIC 1.95 μg/mL).